Islamic Education Teachers’ Technological Pedagogical Content Knowledge (TPACK): A Study in Indonesia - Eliyanto; Erry Yulian Triblas Adesta; Siti Fatimah (Edukasia Islamika : Jurnal Pendidikan Islam, 2021)
This study aims to analyze the knowledge ability of Islamic education teachers about TPACK knowledge. This research is a qualitative research that involved 25 Islamic education teachers from various schools in Kebumen regency as the research subject. The instruments that used in this study were observation sheets and interview sheets. The data analysis technique which used was the model developed by Miles and Huberman, namely data collection, data reduction, data display, and conclusions. The results of the study prove that the knowledge of Islamic education teachers on TPACK is quite high. However, integrating technology effectively and applying various types of appropriate technology into Islamic religious learning should be improved. Some of the solutions that can be offered are by providing adequate facilities in implementing TPACK, understanding and training of TPACK, and continuous TPACK practices.